Predicting Aberrant Fc-fusion Protein Pharmacokinetics from In Silico Structural Properties and Physiologically Based Pharmacokinetic (PBPK) Modeling - Danilo Tomasoni; Alessio Paris; Roberto Visintainer; Kevin D. Cook; Aochiu Chen; Isabel Figueroa; Veena A. Thomas; Luca Marchetti (The AAPS Journal, 2026)
The fusion of therapeutic proteins to the Fc domain of monoclonal antibodies (mAbs) generally improves the proteins' pharmacokinetic (PK) characteristics, extending in vivo half-lives due to the binding of the Fc domain to the FcRn receptor. Yet, several of these Fc-fusion biologics have been observed to have unexpected rapid clearance associated with non-specific off-target binding. Variability in non-specific clearance is often challenging to predict, not well understood, and ultimately can delay the drug development process. In this investigation, we present a computational approach leveraging in silico protein structural properties to extend a physiologically based pharmacokinetic (PBPK) model of mAbs validated on in vivo plasma PK profiles in mice. Selected model parameters affecting protein half-life have been scaled by analytical functions of a panel of calculated in silico protein properties identified by a novel and ad hoc symbolic regression procedure. The resulting extended model has been successfully validated against an independent set of protein plasma PKs, indicating that it can generalize to novel biologics of the same class. Moreover, the extended PBPK model has a median absolute average fold error (AAFE) of 1.18 (min = 1.09; max = 1.51), where values less than 2 typically indicate a good fit. The results enable the de-risking of aberrant PK behaviors, ultimately leading to the selection of Fc-fusion proteins with increased therapeutic value for patients.

Carbon fluxes and partitioning in Eucalyptus and Pinus plantations across a climatic gradient in Brazil - Fernanda Leite Cunha; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Isaira Leite & Lopes; Yann Nouvellon; Timothy Albaugh; David R. Carter; Rafael Rubilar; Isabel Deliberari; Rachel Cook; Joannès Guillemot; Guerric Le Maire; et al. (Agricultural and Forest Meteorology, 2026)

Improved Estimates of Biomass Expansion Factors and Root‐To‐Shoot Ratios: An Approach for Different Forest Types Across a Climatic Gradient in Brazil - Isáira Leite e Lopes; Otávio Camargo Campoe; Geovanni Malatesta Barros; Anny Francielly Ataide Gonçalves; Gabriela Gonçalves Moreira Matzner; Marco Aurelio Figura; Clayton Alcarde Alvares; Fernanda Leite Cunha; Verônica Boarini Sampaio de Rezende; James Stahl; Josiana Jussara Nazaré Basílio; Hyngrid Jaiely Araújo Félix; et al. (Global Change Biology, 2025)
Advancements in the current state of the art of the key drivers of biomass expansion factor (BEF) and the root‐to‐shoot ratio ( R ) are crucial for producing accurate information on forest biomass and carbon stocks. Hence, we compiled a nationally representative dataset encompassing diverse tree growth stages and climatic gradients. In this study, we propose models to improve BEF and R estimates at the tree level for Eucalyptus and Pinus plantations in Brazil. In general, the BEF values were more representative (91.7%) in the database than the R values (8.3%) due to the high cost of collecting coarse roots. Regarding genera, Eucalyptus was more extensively sampled (89.9%) than Pinus (10.1%), reflecting the predominance of Eucalyptus as the most widely planted genus in Brazil. The average BEF and R values calculated in this study were 1.16 and 0.22, respectively, for Eucalyptus spp. and 1.22 and 0.31, respectively, for Pinus spp. In predicting the BEFs, the random effects in the linear mixed model that significantly captured the variations in Eucalyptus and Pinus spp. were temperature and age class, respectively. The fixed effects for Eucalyptus spp. included diameter, height, and age, while for Pinus spp., they were the Köppen climate classification, species, slenderness degree, and age. R estimates were mainly influenced by precipitation and age for both genera, with slenderness and diameter specifically affecting Eucalyptus spp., and height being a driving factor for Pinus spp. Our findings discourage the use of fixed or default values for BEF and R across locations with different climates and growing conditions to reduce uncertainties in carbon accounting and greenhouse gas inventories.

Interaction with B-type lamin reveals the function of Drosophila Keap1 xenobiotic response factor in nuclear architecture - Jennifer Carlson; Emma Neidviecky; Isabel Cook; Bethany Cross; Huai Deng (Molecular Biology Reports, 2024)

Growth kinetics of Bacillus cytotoxicus in liquid Egg yolk during treatment with phospholipase A2 – A one-step global dynamic analysis - Lihan Huang; Nurul Hawa Ahmad; Vijay Juneja; Erika Stapp-Kamotani; Jose Gabiola; Udit Minocha; Robert Phillips; Marie Hooker; Isabel Walls; Kim Cook; James Lindsay (Food Microbiology, 2024)

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Development and Implementation of a Biometrics Device Design Project in an Introductory BME Course to Support Student Wellness - Isabel Miller; Sara Lamer; Aidan Brougham-Cook; Karin J. Jensen; Holly M. Golecki (Biomedical Engineering Education, 2022)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Positive Welfare for Fishes: Rationale and Areas for Future Study - Isabel Fife-Cook; Becca Franks (Fishes, 2019)
Traditional animal welfare paradigms have focused on maintaining physical health and mitigating negative impacts to wellbeing. Recently, however, the field has increasingly recognized the importance of positive welfare (i.e., mental and physical states that exceed what is necessary for immediate survival) and accordingly introduced manipulations and indicators of positive welfare for use in agriculture, laboratories, and zoos/aquaria. The creation and monitoring of positive welfare requires an in-depth knowledge of species-specific behavior and biology, which necessitates species-specific or, at a minimum, taxa-specific standards. Research on positive welfare in fish is lagging in this regard and therefore merits further consideration. In this paper, we aim to merge what is already known about positive welfare with the existing fish behavior literature to develop a plan of action for fish welfare research that will ultimately contribute to the development of positive welfare standards and assessment strategies for fish. We begin by exploring the origins of positive welfare research and then outline the physical, psychological and species-specific areas of inquiry that can be investigated in fish. In addition to presenting current findings on fish motivation, emotion, potential sources of positive welfare such as fulfillment of motivational urges (establishing agency, engaging in exploration and learning), and play behavior, we also identify promising areas for future research aimed at developing accurate and appropriate indicators of positive welfare in fish.